FCSIT announcement supporting system (FASS) - Thavamani, d/o Muniandy (Universiti Malaysia Sarawak, UNIMAS, 2006)
This individual project essentially involved a study into the existing announcement system at Faculty Computer Science of Information Technology (FCSIT) of University Malaysia Sarawak (UNIMAS) in order to design and implement a web-based announcement supporting system to support the existing system. The weaknesses of the existing manual/paper based announcement system had been studied carefully during the analysis phase. The comparisons have also been made between different types of announcement system widely practiced in the some overseas universities through literature reviews. These enabled to solve the current problems and also to discover some new ideas that can be incorporated into the supporting announcement system. Based on this study, a supporting announcement system had been developed as a new innovation to enhance the capacity and functionality of the existing announcement system by providing an alternative way to the lecturers to do announcements via online FCSIT Announcement Supporting System (FASS). Four main softwares were used to develop the system; WINDOWS as an Operating System, PHP as a main scripting tool for coding the system and the Graphical User Interface (GUI), Mysql for database as well as Apache a robust and secure web server had been selected. Therefore, the main objective of this project was to develop an online announcement supporting system and also to study about email and SMS approaches for future enhancements of the system. A few types of testing had been conducted during the system design phase to ensure that the system working properly. Finally, several recommendations for future works had been stated at the end of the report.